Caregiver Burden and Depression in Parents of Children with Chronic Diseases - Şenay Güven Baysal; Seniha Çorabay (AVES Yayincilik, 2024)
Objective: Caregiver burden is a factor that caregivers undertake for patients with chronic diseases and individuals in need of care. Depending on the symptoms of the disease and the processes following the diagnosis, depression problems may develop in caregivers. In this study, it was aimed at determining the caregiving burden of parents who have children with chronic diseases, the condition of special needs, and the factors that affect this burden. Materials and Methods: This study is a descriptive cross-sectional study conducted with 206 parents of children who had been diagnosed with a chronic disease for at least 1 year. The sociodemographic data, the Patient Health Questionnaire 2 & 9, and the Burden Scale for Family Caregivers were provided to the parents. Results: Eighty-four of the participants had little or no caregiver burden, while 122 had moderate and severe caregiver burden. The mean caregiving burden score of mothers was higher (P = .004). Fathers' caregiver burden scores varied depending on the level of education (P = .031). Caregiving burden score was found to differ according to income level (P < .001). The mean caregiving burden score of individuals with chronic disease in the family was higher (P < .001). It was determined that individuals with higher Patient Health Questionnaire 2 and 9 scores and those who did not receive psychological support were higher (P < .001). Conclusion: Parents who are providing care for children with chronic diseases should be supported and closely monitored for signs of depression.